Analysing AI-generated luxury fashion: The perceived value and customer’s purchase intention - Bilro, R. G.; Loureiro, S. M. C.; Matias, M. (2024 Global Fashion Management Conference at Milan, 2024)
AI-generated luxury apparel poses a significant challenge to the traditional conventions of creativity and design. This research offers a distinctive opportunity to investigate the intersection of human and artificial intelligence creative processes while evaluating consumer perceptions and valuing these transformative innovations. In a period characterised by heightened apprehensions over generative AI, the investigation of consumer perceived value and willingness to purchase AI-generated luxury apparel holds significant relevance.